2015
DOI: 10.5194/angeo-33-829-2015
|View full text |Cite
|
Sign up to set email alerts
|

Estimating along-track plasma drift speed from electron density measurements by the three Swarm satellites

Abstract: Abstract. Plasma convection in the high-latitude ionosphere provides important information about magnetosphereionosphere-thermosphere coupling. In this study we estimate the along-track component of plasma convection within and around the polar cap, using electron density profiles measured by the three Swarm satellites. The velocity values estimated from the two different satellite pairs agree with each other. In both hemispheres the estimated velocity is generally anti-sunward, especially for higher speeds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Another possible application is to derive along‐track plasma convection speed V from cross‐correlating magnetic field structures on Swarm A and Swarm C. Assuming that plasma structures remain static during the time it takes for the two satellites to cross them, the plasma motion can be derived by comparing the observed delay Δ τ , found from cross correlation, to the actual time lag between the two satellites Δ t : V=normalΔτnormalΔtnormalΔτvs, where v s is the speed of the satellites and V is positive when the convection is in the same direction as the satellites. Park et al () demonstrated this principle using Swarm density measurements from the first few months of the mission, when all three satellites were in a pearl‐on‐a‐string configuration with Δ t between 1 and 3 min. They noted that with Δ t ≈5 s, which is the case in the current constellation, the 2‐Hz sampling rate of plasma density is too low to give precise estimates of the convection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible application is to derive along‐track plasma convection speed V from cross‐correlating magnetic field structures on Swarm A and Swarm C. Assuming that plasma structures remain static during the time it takes for the two satellites to cross them, the plasma motion can be derived by comparing the observed delay Δ τ , found from cross correlation, to the actual time lag between the two satellites Δ t : V=normalΔτnormalΔtnormalΔτvs, where v s is the speed of the satellites and V is positive when the convection is in the same direction as the satellites. Park et al () demonstrated this principle using Swarm density measurements from the first few months of the mission, when all three satellites were in a pearl‐on‐a‐string configuration with Δ t between 1 and 3 min. They noted that with Δ t ≈5 s, which is the case in the current constellation, the 2‐Hz sampling rate of plasma density is too low to give precise estimates of the convection.…”
Section: Discussionmentioning
confidence: 99%
“…where v s is the speed of the satellites and V is positive when the convection is in the same direction as the satellites. Park et al (2015) demonstrated this principle using Swarm density measurements from the first few months of the mission, when all three satellites were in a pearl-on-a-string configuration with Δt between 1 and 3 min. They noted that with Δt ≈ 5 s, which is the case in the current constellation, the 2-Hz sampling rate of plasma density is too low to give precise estimates of the convection.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Plasma motion in the high-latitude ionosphere provides important information about magnetosphere-ionosphere-thermosphere coupling. Park et al (2015b) estimated the along-track component of plasma convection within and around the polar cap, using electron density profiles measured by the three Swarm satellites. In both hemispheres the estimated velocity was generally anti-sunward and in qualitative agreement with Super Dual Auroral Radar Network (SuperDARN) data.…”
Section: Solar Solar Wind and Magnetospheric Drivers Of Variabilitymentioning
confidence: 99%
“…In addition, the analysis presented here is sensitive to the assumed polar cap convection velocity. In future investigations of plasma structure lifetimes, special care should be taken in treating plasma convection velocity, for example, by using methods of observing plasma drift velocity (Park et al, 2015).…”
Section: Chemical Recombination Ofmentioning
confidence: 99%